2023
DOI: 10.1159/000528815
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Video Fetoscopy: Feasibility and Outcomes of a Novel Modality for Laser Therapy in Twin-to-Twin Transfusion Syndrome Presenting with Inaccessible Anterior Placenta

Abstract: Introduction: Identification of intertwin anastomosis may be challenging during fetoscopy in cases with complete anterior placenta. The aim of this study was to describe the technique, feasibility and outcomes of flexible video fetoscopy for laser coagulation in monochorionic (MC) twin pregnancies with twin-to-twin transfusion syndrome (TTTS) presenting with inaccessible anterior placenta. Methods: From April 2021 to March 2022, a prospective cohort of consecutive MC twin pregnancies complicated with TTTS, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Some cases can even be considered inaccessible with conventional fetoscopy [20, 21]. Although no additional difficulties have been reported with anterior placentas neither in our study nor in the previous studies reporting FLC after 26 weeks, our recently reported technique using a high-resolution flexible scope, which allows good visualization and perpendicular firing angle of the vascular anastomoses in anterior placentas, may be an option to overcome such limitation [6].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Some cases can even be considered inaccessible with conventional fetoscopy [20, 21]. Although no additional difficulties have been reported with anterior placentas neither in our study nor in the previous studies reporting FLC after 26 weeks, our recently reported technique using a high-resolution flexible scope, which allows good visualization and perpendicular firing angle of the vascular anastomoses in anterior placentas, may be an option to overcome such limitation [6].…”
Section: Discussionmentioning
confidence: 78%
“…Since then, the surgical technique for FLC has been refined over the years, aided by the technological advances in endoscopic instruments [5, 6], but little has changed regarding the surgical window. The Food and Drug Administration (FDA) in the USA approved in 2006 the use of the fetoscope under the Humanitarian Device Exemption Program for the treatment of TTTS exclusively “between 16 and 26 weeks,” adding possible legal consequences to its use out of that GA window [7], and therefore, FLC has long been confined to cases presenting before 26 weeks.…”
Section: Introductionmentioning
confidence: 99%